Pengembangan Media Pembelajaran Kimia Menggunakan Lectora Inspire Berbasis STEM Pada Materi Termokimia Kelas XI SMA N 1 Kec. Akabiluru - maya sari (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2021)
Abstract. The main problem in this study is related to the lack of creativity of educators in using learning media, especially in the manufacture and development of media in the learning process. Where the media used by educators during the learning process does not attract students' interest in learning so that it affects the learning outcomes of these students. Thus, it is necessary to have a learning media that can be used by educators and students, namely in the form of learning media using STEM-based Lectora Inspire Software. The purpose of this study is to determine the learning media using STEM-based Lectora Inspire on valid and practical thermochemical material. The type of research used is research and development (Research and Development) with a 4D design model. This research consists of four stages, namely: define, design, development and disseminate stage. However, this research was only carried out until the development stage due to the limited time required Based on the results of the study, it was shown that the product in the form of learning media using STEM-based Lectora Inspire that was developed was valid and practical. The results of product validity obtained a percentage of 98.8% with very valid criteria, and the percentage of practicality through student response questionnaires obtained a percentage of 73.1% with practical criteria. Based on these data, the STEM-based Lectora Inspire learning media is feasible and can be used as a medium in the learning process Keywords: Lectora Inspire, STEM, dan Termokimia